Caracterização de atividade ATPásica de Miosina V de cérebro de rato obtida por congelamento - Melo, Hugo Christiano Soares (2003)
We recently obtained a fraction enriched in Mg2 + -ATPasic activity from frozen rat brain cytosol. Our goal in this paper was to analyze this ATPase and characterize it. Our procedures were rat brain extraction, immediate homogenization in 50 mM Imidazole-HCI pH 8.0 buffer; 10 mM EDTA; 1.0 mM DTT and protease inhibitors (1% Aprotinin and 1 mM Benzamidine), centrifugation at 45000xg for 40 minutes at 4 ° C and freezing the soluble fraction at -20 ° C. After a minimum of 48 hours this fraction was thawed and then centrifuged again at 45000xg for 40 minutes at 4 ° C. The precipitated fraction was resuspended and centrifuged again under the same conditions as above. The precipitated fraction is enriched in Mg2 + -ATPase activity and SDS-PAGE analysis showed three main polypeptides, one with high molecular weight similar to myosin heavy chain and two with corresponding molecular weight at 57 and 45 kDa. The high molecular weight polypeptide was labeled with myosin V specific antibody. The 57 kDa polypeptide was solubilized with 0.2% Triton X-100, with the high molecular weight polypeptide and 45 kDa polypeptide being precipitated. The Mg2 + -ATPasic activity of this precipitate is three times lower than the precipitate obtained without triton X-100. Our fraction showed no stimulation of Mg2 + -ATPasic activity by Ca2 + and Calmodulin, having only a low K + / EDTA-ATPasic activity when compared to Mg2 + -ATPasic activity. Ca2 + -ATPasic activity was about 80% of Mg2 + -ATPasic activity. There was also no change in Mg2 + -ATPasic activity by aluminum chloride, sodium fluoride or aluminum fluoride. Vanadate (50, 200 and 1000 pM) or azide (1 mM) did not inhibit this activity either. This fraction showed hydrolysis preference for ATP, however it also hydrolyzed ADP (40%) and GTP (60%), but not AMP, AMP-PNP, PPj, ADP2'5'3,5 AMP-PNP inhibited Mg2 + -ATPasic activity. . Mg2 + -ATPasic activity was inhibited about 50% by Fe2 + at a concentration of less than 1 mM, but not by copper, cobalt or zinc cations. Trypsin protein digestion caused a loss of activity and degradation of the high molecular weight polypeptide, keeping the 45 kDa polypeptide intact in our fraction. In this paper we describe a simple method for obtaining myosin V from a soluble rat brain fraction however was not stimulated by Ca2 + / Calmodulin and did not express K + / EDTA-ATPasic activity.